2015
DOI: 10.1080/01494929.2015.1031425
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Difficulties Among U.K. Military Personnel: Impact of Sociodemographic, Military, and Deployment-Related Factors

Abstract: Military work, especially operational deployments, may impact the romantic relationships of military personnel. Using a subsample of 7,581 participants from a cohort study of U.K. military personnel (data collected between 2007 and 2009), the prevalence of relationship difficulties and associations with sociodemographic, military-, and deployment-related characteristics was examined. Most participants did not report experiencing relationship difficulties. Adjusted regression analyses indicate that childhood ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Marketplace exclusion may also arise due to the unpredictable nature of roles within the Armed Forces. Military work schedules are typically subject to change at short notice and extended periods of absence are also common (Keeling et al, 2015;Park, 2011). This has a far reaching impact on our participants' marketplace access; for example, they described the difficulties they faced making holiday arrangements: "I would love to book a holiday in September for the following summer and get my child free spaces and pay it off month by month, but how can I do that when I don't know what's going to happen next August?…”
Section: Marketplace Challenges and The Potential For Marketplace Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marketplace exclusion may also arise due to the unpredictable nature of roles within the Armed Forces. Military work schedules are typically subject to change at short notice and extended periods of absence are also common (Keeling et al, 2015;Park, 2011). This has a far reaching impact on our participants' marketplace access; for example, they described the difficulties they faced making holiday arrangements: "I would love to book a holiday in September for the following summer and get my child free spaces and pay it off month by month, but how can I do that when I don't know what's going to happen next August?…”
Section: Marketplace Challenges and The Potential For Marketplace Exclusionmentioning
confidence: 99%
“…These factors also impact their spouses and partners (numbering in excess of 100,000 in the UK) (Ministry of Defence, 2018a; 2018b) who face regular relocation with accompanying disruptions to their social networks and employment. They must also manage the daily challenges associated with their partner's unpredictable working commitments alongside potential anxieties associated with the risk of harm to their serving partner (Keeling et al, 2015). Military spouses and partners represent key stakeholders for the UK Armed Forces and their resulting negative attitudes towards the military establishment can have a detrimental impact on serving personnel's performance, morale, and retention in role (Park 2011;Rosen et al 1989).Statistics also indicate that the most frequently cited reason for premature retirement from a military career is the impact of service on family and personal life (Ministry of Defence, 2018b).This study complements the wealth of research into the wellbeing of military personnel (e.g.…”
mentioning
confidence: 99%
“…Research suggests that the impact of military life, deployment and leaving the army can have a significant impact on families and on spouses too. 24,25 Although romantic relationship problems are reportedly more likely in military personnel compared to the general population, 26 this study found that only half of all respondents agreed that this was a need. Veterans did not see the value in providing loved ones with information to help them better support the veteran.…”
Section: Discussionmentioning
confidence: 63%
“…As compared to civilian couples, military couples have a number of undeniable strengths in their favor, along with challenges that might have more of an impact on relationship satisfaction and stability. Steady employment, financial security, and subsidized health care and counseling services might be judged as strengths (Bakhurst, Loew, McGuire, Halford, & Markman, ; Karney, Loughran, & Pollard, ; Keeling, Wessely, Dandeker, Jones, & Fear, ). On the other hand, the challenges facing military couples can include frequent relocation and possible financial or housing insecurity, long and/or frequent separations from partners and other loved ones due to deployment, along with combat exposure and its associated health hazards, such as posttraumatic stress disorder (PTSD) and intimate partner violence (Allen, Rhoades, Stanley, & Markman, ; Foran, Wright, & Wood, ; Reddy, Meis, Erbes, Polusny, & Compton, ; Renshaw et al., ).…”
Section: Relationship Education Programs For Military Couplesmentioning
confidence: 99%
“…Findings from previous studies (Bakhurst, Loew et al., ; Bakhurst, McGuire et al., ; Stanley et al., ) might fall short of expectations because no impact on relationship satisfaction indices was found with respect to RE programs adapted for military couples. In addition, the majority of military couples were satisfied with their relationships (Foran et al., ; Karney & Crown, ; Keeling et al., ) such that they might not need any intensive support, whereas others who were already distressed and might engage in infidelity were separated or divorced postdeployment (Balderrama‐Durbin et al., ). Further possible reasons for the apparent contradiction are discussed in Stanley et al.…”
Section: Relationship Education Programs For Military Couplesmentioning
confidence: 99%